2018
DOI: 10.1002/ajmg.a.38613
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude, protective buffering, and cognitive dissonance: How families respond to pediatric whole exome sequencing in the absence of actionable results

Abstract: Clinical genome and exome sequencing (CGES) may identify variants leading to targeted management of existing conditions. Yet, CGES often fails to identify pathogenic diagnostic variants and introduces uncertainties by detecting variants of uncertain significance (VUS) and secondary findings. This study investigated how families understand findings and adjust their perspectives on CGES. As part of NIH's Clinical Sequencing Exploratory Research Consortium, children were recruited from clinics at the Children's H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…This is particularly important given that research has shown that while this group is interested in and willing to undertake genetic testing, they have concerns about the implications of testing and the potential risks and limitations . An important limitation of the technology is that currently around 60% of paediatric patients do not get a diagnosis from GS which may lead to feelings of frustration and disappointment . Studies have also shown that age may play a factor in young people's understanding of genetics as well as whether there is a family history of a genetic condition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important given that research has shown that while this group is interested in and willing to undertake genetic testing, they have concerns about the implications of testing and the potential risks and limitations . An important limitation of the technology is that currently around 60% of paediatric patients do not get a diagnosis from GS which may lead to feelings of frustration and disappointment . Studies have also shown that age may play a factor in young people's understanding of genetics as well as whether there is a family history of a genetic condition .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly which may lead to feelings of frustration and disappointment. 24,25 Studies have also shown that age may play a factor in young people's understanding of genetics 26 as well as whether there is a family history of a genetic condition. 27 Using this measure, health professionals may be able to identify those young people that might have limited knowledge or misunderstandings about WGS and who may therefore require more in-depth counselling or information provision.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors include biological and legal ties, geographic and emotional proximity, and assumptions about risk status (Dancyger et al, 2010; Koehly, 2017; Padamsee, Muraveva, Yee, Wills, & Paskett, 2017; Rodriguez, Corona, Bodurtha, & Quillin, 2016; Sinicrope et al, 2009). What information is shared, and when, may be influenced by the developmental capacity of the information recipient and emotional valence of the relationship (Dancyger et al, 2011), and could lead to incomplete, inaccurate, or delayed information sharing (Werner-Lin, Zaspel, et al, 2018; Young et al, 2017).…”
Section: Overview Of Hereditary Cancer Risk Communication Researchmentioning
confidence: 99%
“…Genetic and oncology health professionals must concurrently contend with the clinical complexity of LFS—with its varied, difficult‐to‐manage phenotype—and the normative developmental changes that impact how individuals at high risk of cancer live with LFS in family life from a young age. These changes center around growing capacity for autonomous decision‐making regarding genetic testing, with varying levels of family involvement; cognitive capacity to understand the short‐ and long‐term implications of genetic testing and risk management; decision‐making and engagement with risk management and/or risk‐reducing strategies; health literacy; how they identify, label, and manage emotional responses; existential awareness; and confidence in navigating the healthcare system (Duncan & Young, ; Forbes Shepherd et al, ; Pichini et al, ; Werner‐Lin et al, ). Similar clinical and psychosocial challenges are also common for other early‐onset multi‐organ conditions with complex screening protocols, for example, von Hippel–Lindau syndrome (VHL), multiple endocrine neoplasia 1 (MEN1), neurofibromatosis, constitutional mismatch repair deficiency (CMMRD), and emerging conditions like DICER1 syndrome.…”
Section: Introductionmentioning
confidence: 99%